Enhanced photocatalytic degradation of psychoactive substances using amine-modified elongated titanate nanostructures. Issue 2 (11th December 2017) - Barrocas, B.; Neves, M. C.; Conceição Oliveira, M.; Monteiro, O. C.
Abstract : Novel titanate nanotubes sensitized with ethylenediamine demonstrated promising photocatalytic performances for the degradation of psychoactive substances, caffeine and theophylline, and phenol removal. Abstract : Many thousands of pharmaceuticals and personal care products (PPCPs) are used worldwide and disposed in the environment after use. Several removal methodologies have been proposed but clear improvements in effectiveness and efficiency are needed. In this work, new hybrid photocatalytic nanomaterials were obtained through sensitization of titanate nanotubes (TNT) and nanowires (TNW) with ethylenediamine (EDAmine). The prepared materials, NTNT and NTNW respectively, were morphologically, structurally, and optically characterized by XRD, TEM, DRS and XPS. No modifications in the structure and morphology were detected after EDAmine incorporation. However, an increase in the visible light absorption and in the point of zero charge was observed. The application of these novel hybrid nanomaterials in the catalytic photodegradation of emergent pollutants was studied. Terephthalic acid was used as a probe for hydroxyl radical photocatalytic production evaluation. The highest catalytic activity was achieved by the NTNT sample. The photocatalytic ability of the hybrid materials for the degradation of psychoactive substances, caffeine and theophylline, and for phenol removal was evaluated and the secondary products identified. After 60 min under UV-vis radiation, the NTNT sample was the best catalyst, achieving 98% photodegradation efficiency for phenol and theophylline and 60% for caffeine (20 ppm solutions). A mechanism for charge transfer in irradiated NTNT is proposed and discussed.